DROGADICCIÓN: LOS HIJOS DE LA NEGACIÓN - Valverde Obando, Luis A. (2023)
In the treatment of addicts to the alcohol and other drugs and their relatives, the authors have observed that one of the big difficulties of the families to achieve the rehabilitation of a drug addict is that they know what they want like goal, but they don’t know how to achieve it. This reproduces the same square that the addict faces, when all they tell him that he stops to drink or to consume substances, but nobody tells him how to make it. Leaving of that context, and involving to the addict and their family, it is approached in this article a first step of the recovery in the sharp phase of the illness: the mechanism of the negation. This mechanism is appropriated in the family dynamics as characteristic one of its main ones, affecting all the members; particularly to the children to who it is denominated as the children of the negation, because today the children of the addicts, by means of the mechanism of the negation, behave as dry addicts (that don’t consume), but tomorrow they will be the reproductive active addicts of the family patterns.